2008
DOI: 10.1007/s10554-008-9338-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of volumetric intravascular ultrasound radiofrequency-based analysis of coronary plaque composition in vivo

Abstract: Intravascular ultrasound radiofrequency (RF-IVUS) data permit the analysis of coronary plaque composition in vivo and is used as an endpoint of ongoing pharmacological intervention trials. We assessed the reproducibility of volumetric RF-IVUS analyses in mild-to-moderately diseased atherosclerotic human coronary arteries in vivo. A total of 9,212 IVUS analyses on cross-sectional IVUS frames was performed to evaluate the reproducibility of volumetric RF-IVUS measurements in 33 coronary segments with a length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Studies have shown good reproducibility of volumetric IVUS radiofrequency-based analysis of coronary plaque composition in vivo [20]. IVUS and angioscopy studies have also indicated that reduction of lesion volume and relative content changes (e.g., early loss of yellow color by angioscopy) may both reduce plaque vulnerability in an additive manner [21].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown good reproducibility of volumetric IVUS radiofrequency-based analysis of coronary plaque composition in vivo [20]. IVUS and angioscopy studies have also indicated that reduction of lesion volume and relative content changes (e.g., early loss of yellow color by angioscopy) may both reduce plaque vulnerability in an additive manner [21].…”
Section: Discussionmentioning
confidence: 98%
“…Nair et al (7), in a histological study, reported that VH-IVUS had an 80% to 92% accuracy for identification of coronary plaque DC, NC, FF, or FT. Subsequent studies demonstrated the high reproducibility of VH-IVUS analyses (11,12). Hartmann et al (12) showed that the relative difference of volumetric VH-IVUS analysis in repeated pull-backs was Ͻ1% for NC and Ͻ3% for DC, FF, and FT.…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) can analyse plaque composition and indentify calcium. 13,14 Nevertheless, as the identification of thrombus by IVUS is limited and introduction of the imaging probe can induce distal embolisation, operators may sometimes -in case of doubt -chose for direct use of an aspiration catheter. Optical coherence tomography (OCT) may be an alternative imaging technique to distinguish between thrombus and calcified lesions.…”
Section: Results Of Thrombus Aspirationmentioning
confidence: 99%